Advancing Equity Through Centering Societal Values to Operationalize Racism as a Public Health Crisis: The KKey Values Inequities Model (Health Equity, 2023)
Background: The past two decades have been marked by increased efforts to advance equity in various disciplines, including social sciences, public health, environmental health, and medicine. In 2020, a national movement of municipalities declared racism a public health crisis. These efforts have coincided and likely shaped a growing sphere of federal and philanthropic funding for health equity, which frequently calls for practical interventions toward reducing and ultimately eliminating disparities. Disparities in health such as maternal mortality, infant mortality, diabetes, cancer, and stroke have been linked to root causes such as racism. Often, root causes are also linked to disparities in other sectors (i.e., finance/wealth attainment, educational attainment, career attainment, and home ownership). In 2021, in a study published in the New England Journal of Medicine, suggested that racist policies were root causes of U.S. racial health inequities. While racism, sexism, and classism, etc., are characterized as root causes, we posit that there is a deeper driver that has yet to be advanced. This presents a disparity?inequity model that maps disparities and inequities to the societal value system, not root causes. Methods: The KKey Values Inequities Disparities Model described in this article combines a case study of the Flint Water Crisis to explore the historic impact of human devaluation and its role in systemic racism and classism, which ultimately creates and exacerbates inequities that produce disparities in communities. The model integrates the value system and its contribution to societal causes (formerly known as root causes). Conclusions: A broadly defined values?inequities?disparities model will allow researchers, practitioners, decision makers, lawmakers, and community members to (1) assess the core root of inequities and disparities; (2) identify solutions in the human value domain; (3) design appropriate course corrective programming, interventions, processes, and procedures; and (4) create actions to integrate new systemic procedures and practices in our laws and governance to advance equity.